2001
DOI: 10.1007/bf02723198
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function tests in beta thalassemia

Abstract: To study pulmonary function tests (PFT) in multiple transfusion recipient thalassemics, PFTs were done for 30 thalassemics and 20 matched controls. Confirmed cases of thalassemia on regular transfusion therapy were the subject of study. Apart from history and physical examination of the thalassemics, serum ferritin estimation and spirometry were done. Parameters studied included lung volumes--functional residual capacity (FRC), forced vital capacity (FVC), residual volume (RV) and total lung capacity (TLC); an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
2
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 10 publications
2
15
2
13
Order By: Relevance
“…But this treatment has some complications, such as progressive iron deposition in vital organs, which impairs their functions [3]. There are some debates about abnormalities of respiratory function and causes of its dysfunction [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…But this treatment has some complications, such as progressive iron deposition in vital organs, which impairs their functions [3]. There are some debates about abnormalities of respiratory function and causes of its dysfunction [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Akciğerlerdeki demir depolanması teorik olarak serum ferritin düzeyi ve karaciğerdeki demir depoları ile bağlantılıdır 76 . Serum ferritin düzeyi şelasyon tedavisinin takibinde en sık kullanılan parametre olmasına rağmen bazı yayınlarda total demir yükünü tam olarak yansıtmadığı bildirilmiştir 80 .…”
Section: Solunum Sistemi Bulgularıunclassified
“…Guidotti ve arkadaşları tarafından yapılan çalışmada ise, β -TM'li hastalarda %35.6 oranında restriktif bozukluk saptanmış ve serum ferritin düzeyleri ile restriktif patern arasında anlamlı ilişki olduğu bildirilmiştir 97 . Arora ve arkadaşlarının yaptığı bir çalışmada ise karaciğer demir yükünün non-invazif bir göstergesi olduğu düşünülen serum ferritin değerinin solunum fonksiyon testi anormalliği üzerine zayıf etkisi olduğu gösterilmiştir (p=0.07) 76 .…”
Section: Solunum Sistemi Bulgularıunclassified
See 1 more Smart Citation
“…Previous studies have reported pulmonary dysfunction in patients with β-thalassemia (Thal); mostly with restrictive impairment (RI) in patients being transfusion-dependent [1][2][3][4][5][6][7][8][9][10][11] and also in non-transfusion dependent patients. [12][13][14] Other pulmonary abnormalities consist of small airway obstruction, 12,15 impairment of diffusion capacity, 16,17 arterial hypoxemia, 16,18 and pulmonary hypertension (PH).…”
Section: Introductionmentioning
confidence: 99%